The Role of Identifying the Lexical Relations among Target Vocabulary Words through Blended Learning on EFL Students’ Mastery in Using Target Vocabulary - Alameh, Sahar Hussein Aboud (European Scientific Journal, ESJ, 2018)
This paper examines the effect of identifying the lexical relations among target vocabulary items through a blended learning approach on improving EFL students’ mastery in using target vocabulary. At first, this study aims at showing how the difficulties in using lexical units from a semantic perspective result in the production of erroneous sentences and consequently affect the collaborative process of communication. The current study will use an experimental approach, a true experiment, to analyze the data and verify the results of using various online and offline instruction and tasks with the goal of improving students’ lexical awareness and development to master the target vocabulary. A total of 60 students sharing a similar social and educational background were randomly assigned to the experiment. The experimental group studied the target vocabulary items through blended learning strategies while the control group learned the same target vocabulary items through traditional way of teaching. After the traditional in class instruction period, a paper-based vocabulary test was administered to both groups of students; however, the experimental group which was made up of 30 students from the same section was taught the same target vocabulary items for a period of 4 weeks through blending task-based DDL instruction and in class instruction. The results of the study indicate that EFL students at LIU (Lebanese International University) make substitutional (synonym) lexical errors frequently; however, the results of the experimental group after receiving the blended pedagogic intervention with a systematic lexical and communicative approach surpassed their results before receiving the treatment. That is why students in the posttest showed a broader ability to produce a well-structured written text and comprehend a reading text as well.